Transactional Analysis and the Ludic Third (TALT): A Model of Functionally Fluent Reflective Play Practice. (3rd July 2018) - King, Pete; Temple, Susannah
Abstract: This article presents a new theoretical model of the play interaction between children and playworkers: transactional analysis and the ludic third (TALT). The importance of reflective professional practice as a key aspect of the TALT model is emphasized. The transactional analysis concepts of the integrating Adult ego state and functional fluency are presented to show how they are put to use both in reflective practice and for underpinning the vital concept of the witness position aspect of the play process. The values of knowledgeable, sensitive, and above all active responsiveness from the witness position are explained with short case studies. This active role is discussed with regard to the concepts of potential space and the ludic third . The authors suggest that TALT has implications for all professionals who work with children in a play context. They also consider the potential for children to develop reflective skills as they play.